Effects of crossing and environmental factors on production and some constituents of milk Ossimi and Saidi sheep and their crosses with Chios - Hassan, H.A. (Elsevier, 1995)
Milk Production and milk constituents were studied in 95 ewes of two purebred groups, Ossimi(O) and Saidi (S), and two F1crosses with Chios(C) (CO and CS) from September 1991 to April 1993 at the Experimental Animal Farm, Faculty of Agriculture, Minia University, Egypt. Breed of ewe had an effect (p